Open Source Compliance and Goldilocks: Too Little, Too Much, Just Right (Journal of Open Law, Technology & Society, 2020)
Although open source compliance can be tricky and require resources it is not inherently necessary to employ dedicated personnel and enterprise solutions to accomplish a reasonable degree of best practices. This is particularly in situations where any resource allocation will compete for the resources required to actually create a product.